BASIC PRINCIPLES OF OPERATION AND ENERGY BALANCE OF VOLUME HYDRAULIC DRIVE - YANISHEVSKYY, Vasyl (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Scientific and technological progress in mechanical engineering is inextricably linked with the development and creation of new, more productive, more efficient equipment and the improvement of the designs of existing machines and equipment. The technical level of machines is largely determined by the perfection of the power flow drive to their working bodies. In this case, an important role is given to drives, in which the energy carrier is liquid. Such drives are called hydraulic or hydraulic drives. The use of hydraulic drives allows you to create progressive designs of machines, expand the possibilities of mechanization and automation of technological processes, to facilitate the working conditions of operators, to improve the culture of material production. Currently, hydraulic actuators are successfully used in almost all areas of industrial production, including in the construction, road, and municipal engineering industries. Small overall dimensions and weight with a significant generated power, high overload capacity in terms of power and torque, the ability to provide sufficiently large gear ratios and stepless speed control of the output link, easy reversibility, which ensures high speed and accuracy of processing control actions, the availability of automation - these are the main advantages of the hydraulic drive, which predetermine its wide application in the construction of transport and technological machines. The article defines the basic principles of the volumetric hydraulic drive, what values and indicators affect them. A goal has been defined regarding basic information about hydrostatic drives, devices and the principle of operation of hydraulic mechanisms and hydraulic devices, drawing up hydraulic circuit diagrams, the sequence of calculating a hydraulic drive and choosing hydraulic elements. The energy capabilities of the hydraulic drive, characterized by its power, are also determined.